Comparative expression analysis of water buffalo (Bubalus bubalis) to identify genes associated with economically important traits - Mishra, Dwijesh Chandra; Bhati, Jyotika; Yadav, Sunita; Avashthi, Himanshu; Sikka, Poonam; Jerome, Andonissamy; Balhara, Ashok Kumar; Singh, Inderjeet; Rai, Anil; Chaturvedi, Krishna Kumar (Frontiers in Veterinary Science, 2023)
Domestic water buffalo (Bubalus bubalis) milk, meat, skins, and draught power contribute significantly to the worldwide agricultural economy. The world's water buffalo population is primarily found in Asia, and the buffalo supports more people per capita than any other livestock species. For evaluating the workflow, output rate, and completeness of transcriptome assemblies within and between reference-free (RF) de novo transcriptome and reference-based (RB) datasets, a large number of bioinformatics studies have been carried out to date. However, comprehensive documentation of the degree of consistency and variability of data produced by comparing gene expression levels using these two separate techniques is lacking. In the present study, we assessed the variances in the number of differentially expressed genes (DEGs) attained with RF and RB approaches. Considering this, our study was carried out to identify, annotate and analyse the genes related to four major traits of buffalo viz., milk volume, age at first calving, post-partum cyclicity and feed conversion efficiency. Total of 14201 and 279 DEGs were identified in RF and RB assembly. Moreover, gene ontology (GO) terms of the identified genes were allocated to various traits. These characterized genes will enrich the knowledge of genetic mechanism for improving the productivity of water buffalo through molecular breeding. Our empirical findings suggest significant contributions to answering biological issues about the transcriptome in non-model organisms.